2010
DOI: 10.1002/app.31473
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of colloidal crystals constructed by silica hybrid nanoparticles

Abstract: Silica (SiO 2 )-crosslinked polystyrene (PS) particles possessing photofunctional N,N-diethyldithiocarbamate (DC) groups on their surface were prepared by the free-radical emulsion copolymerization of a mixture of SiO 2 (diameter D n ¼ 192 nm), styrene, divinyl benzene, 4-vinylbenzyl N,N-diethyldithiocarbamate (VBDC), and 2-hydroxyethyl methacrylate with a radical initiator under UV irradiation. In this copolymerization, the inimer VBDC had the formation of a hyperbranched structure by a living radical mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The alternating copolymerization of styrene and maleimide derivatives was chosen as ideal synthetic platform. Previous reports have shown that maleimide-terminated macromonomers form alternating copolymers via copolymerization with styrene 21,22 and styrene macromonomers. [23][24][25][26][27] A BCP terminated with a maleimide should copolymerize with styrene to form a graft BCP with 50% density, and previous work has shown that copolymer composition of styrene/ maleimide copolymers can be finely tuned by adjusting the feed ratio of two different maleimides.…”
mentioning
confidence: 99%
“…The alternating copolymerization of styrene and maleimide derivatives was chosen as ideal synthetic platform. Previous reports have shown that maleimide-terminated macromonomers form alternating copolymers via copolymerization with styrene 21,22 and styrene macromonomers. [23][24][25][26][27] A BCP terminated with a maleimide should copolymerize with styrene to form a graft BCP with 50% density, and previous work has shown that copolymer composition of styrene/ maleimide copolymers can be finely tuned by adjusting the feed ratio of two different maleimides.…”
mentioning
confidence: 99%